UMP’s Centralized Analysis Laboratory already in operation - UMP, PNC (Penerbit UMP, 2010)
The Centralized Analysis Laboratory at Universiti Malaysia Pahang (UMP) is already in a phase-by-phase operation. The idea of a centralized lab first surfaced in the middle of 2009. The plan then was to develop a centralized lab for a variety of technical services- one which provides qualitative analyses, and caters to both internal and external users.